2015
DOI: 10.3390/en8031817
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carbon Electrode Morphology Affect Microbial Fuel Cell Performance with Shewanella oneidensis MR-1

Abstract: Abstract:The formation of biofilm-electrodes is crucial for microbial fuel cell current production because optimal performance is often associated with thick biofilms. However, the influence of the electrode structure and morphology on biofilm formation is only beginning to be investigated. This study provides insight on how changing the electrode morphology affects current production of a pure culture of anode-respiring bacteria. Specifically, an analysis of the effects of carbon fiber electrodes with drastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Carbon based electrodes of different natures are being proposed for biotechnological applications of organisms such as SOMR‐1 . This is a consequence of their chemical and biological inertness in the operating conditions of microbial electrochemical technologies, and their potential for being cheap to produce.…”
Section: Resultssupporting
confidence: 89%
“…Carbon based electrodes of different natures are being proposed for biotechnological applications of organisms such as SOMR‐1 . This is a consequence of their chemical and biological inertness in the operating conditions of microbial electrochemical technologies, and their potential for being cheap to produce.…”
Section: Resultssupporting
confidence: 89%
“…The abundance of Clostridia here in the inoculum and after operation was sustained on the level 10%, but this genus was not the most abundant in the anodic microbial population. However, it has been noted that ability of microorganisms to produce high power densities does not necessarily correlate with their high abundance in the anodic biofilm [61], as abundances can be affected by biomass yields and other factors [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…6). Sigmoidal shaped voltammograms were observed for all anodes suggesting that the current was produced by direct electron transfer from the biofilm [42]. Torres and co-workers demonstrated that the electroactive microorganisms that grown at low anode potentials (-0.150 V vs SHE) carried out extracellular electron transfer exclusively by conducting electrons through the biofilm [38].…”
Section: Electrochemical Characterizationmentioning
confidence: 92%